Congenital syphilis, stillborn twins and placental retention culminating in hysterectomy: case report - Martins, Carolina FN; Silveira, Filomena A; Muzitano, Afonso G; Pereira, Marcus Vinícius C; Souza, Philippe Godefroy C (Brazilian Journal of Sexually Transmitted Diseases, 2007)
Introduction: congenital syphilis is one of the most inappropriate morbidity causes and perinatal mortality, revealing ineffective prenatal care. The intra-uterine infection for the Treponema pallidum can result in stillborn, neonatal death, premature and/or syphilitic lesions that lead to disorders as deafness, neurological damage and bone deformities. It is congenital infection that persists in prominence, although penicillin benzathine G prevents in almost 98% the maternal-fetal transmission, when the mother is treated correctly. Objective: this work presents the case of a twins` gestation that ended up with the death intra-uterus of fetuses, placental retention and shock due to loss of blood, culminating in hysterectomy, witch happened at the Maternity of Hospital School Luiz Gioseffi Jannuzzi, in Valença, Rio de Janeiro. Case report: the case of a 33 year-old patient who belonged to a low socioeconomic class, with several previous childbirths is related, she was admitted in the service in premature birth work, with both fetuses dead intra-uterus. The childbirth was transpelvic, with placental retention and shock due to loss of blood. With ready-attendance done, hysterectomy and the stabilization of the case. VDRL, in cases of internment, revealed to be positive, in the beginning of the treatment. The patient stayed eight days in the hospital. Conclusion: it is evident that syphilis is a disease with serious consequences to pregnant women and their children, since, 80% of infected mothers without treatment, they transmit the disease to the fetuses and several of them die before reaching two years old